2014
DOI: 10.15740/has/arjci/5.2/114-117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting density, irrigation and fertigation levels on water saving and water use efficiency of brinjal (Solanum melongenaL.)

Abstract: A field experiment was conducted during Rabi-hot weather of 2009-2010 at Department of Agronomy, College of Agriculture, Dapoli, Dist. Ratnagiri (M.S.). The soil of experimental field was sandy clay loam in texture and moderately acidic in reaction, medium in available N, low in available P 2 O 5 and high in K 2 O content. The experiment was laid out in Split Plot Design consisted of three planting density viz., S 1 -75×75cm, S 2 -75-50×90cm, S 3 -175-50×50cm and three irrigation levels (I 1 -100 % ET crop , I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…The ultra-density crop facilitate in maintaining the soil fertility status which leads to proper growth and development of crop with producing maximum plant spread. The results corroborate the findings made by Ughade and Mahadkar (2015) [11] in brinjal. Maximum number of branches per plant (4.21) at last harvest was recorded with treatment s 1 (90 cm × 90 cm).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The ultra-density crop facilitate in maintaining the soil fertility status which leads to proper growth and development of crop with producing maximum plant spread. The results corroborate the findings made by Ughade and Mahadkar (2015) [11] in brinjal. Maximum number of branches per plant (4.21) at last harvest was recorded with treatment s 1 (90 cm × 90 cm).…”
Section: Resultssupporting
confidence: 92%
“…With respect to varieties, significantly maximum fruit weight (80.04 g) was recorded with treatment v 1 (GJB3). Ughade and Mahadkar (2015) [11] nicely briefed the, wider spacing recorded statistically higher values of average weight of fruit under study. The maximum number of fruits per plant (28.24) was recorded in treatment s 1 (90 cm ×90 cm) and varieties, significantly maximum number of fruits per plant (32.14) was recorded with treatment v 3 (Doli 5).…”
Section: Resultsmentioning
confidence: 69%
“…While insufficient water inhibits leaf expansion and photosynthetic capacity. Similar results are reported by Ughade and Mahadkar (2015) [18] for brinjal. Whereas, application of different levels of fertigation had non-significant effect on plant spread of chilli at 30 and 60 DAT and found significant at 90 and 120 DAT.…”
Section: Plant Spread (Cm)supporting
confidence: 92%
“…Harmanto et al, (2005) concluded that the drip irrigation at 75% of ETc provided the maximum crop yields and irrigation water productivity in tomato variety Troy 489 under tropical greenhouse conditions. Ughade and Mahadkar (2014) reported that the brinjal crop under Field water use efficiency (FWUE) was maximum under treatment 80% ET with100 % RDF drip fertigation while comparing with 100 and 60% ET with RDF drip fertigation. Patel and Rajput (2007) reported that the potato yield was Maximum when irrigation was applying at the 100% of the crop evapotranspiration (23.6 cm of irrigation water) and by placing the drip tape at 10.0 cm depth followed by 15.0 cm and 20.0 cm depth.…”
Section: Disadvantages Of Drip Irrigationmentioning
confidence: 99%